PERBANDINGAN PENGARUH PEMBERIAN ANALGETIK ETORICOXIB DENGAN NATRIUM DICLOFENAK TERHADAP RASA NYERI PASCA ODONTEKTOMI (IMPAKSI KELAS 1, MOLAR 3 RAHANG BAWAH) - Taufiqurrachman Taufiqurrachman; Kuswartono Mulyo (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Pain is a common complaint and frightening experience for patients post odontektomi so in need of process right and good. Diclofenak natrium analgesic drugs can not always be achieved the maximum in comparison with the type of drug that reaches the maximum etoricoxib appropriately and well.Objective : To determine the meaning of analgesic effect of etoricoxib with diclofenac natrium for pain odontektomi.Methods : This study is a quasi-experimental research design